2018
DOI: 10.7717/peerj.4936
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the ecotoxicity of urban estuarine sediment using benthic and pelagic copepod bioassays

Abstract: Urban estuarine sediments are sinks to a range of contaminants of anthropogenic origin, and a key challenge is to characterize the risk of these compounds to receiving environments. In this study, the toxicity of urban estuarine sediments was tested using acute and chronic bioassays in the benthic harpacticoid Quinquelaophonte sp., and in the planktonic calanoid Gladioferens pectinatus, two New Zealand copepod species. The sediment samples from the estuary tributary sites significantly impacted reproduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…The 3 copepods in our study had similar baseline levels that agreed well with published data for copepods and other zooplankton species (Table ). The within‐treatment variability observed in the present study of single copepods was also within the range observed earlier in studies using pools of up to 120 individuals (Ternjej et al ; Charry et al ). An advantage of studying single copepods is that individual variability in responses to genotoxic insult can be determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The 3 copepods in our study had similar baseline levels that agreed well with published data for copepods and other zooplankton species (Table ). The within‐treatment variability observed in the present study of single copepods was also within the range observed earlier in studies using pools of up to 120 individuals (Ternjej et al ; Charry et al ). An advantage of studying single copepods is that individual variability in responses to genotoxic insult can be determined.…”
Section: Discussionsupporting
confidence: 91%
“…More studies are clearly needed to clarify why copepod cells are so robust to oxidative stress. Earlier studies have addressed genotoxicity in copepods following exposure to cadmium (Pavlaki et al 2016), polluted sediments (Charry et al 2018), and ultraviolet (UV) light (Tartarotti et al 2014). To our knowledge, the present study is the first in which DNA strand breaks in copepods have been quantified following Cu exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of reactive sulfides were measured following US Environmental Protection Agency (USEPA) protocols (SW846 and 9030). At the end of the 6‐d test, naupliar development and survival were assessed by calculating larval development ratio (realized copepodite/[number of copepodites + number of nauplii]) and mortality (Charry et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Gladioferens pectinatus , a pelagic species of calanoid copepod commonly found in New Zealand, was kept in the laboratory in monoculture as described previously. 8 Acute toxicity tests (48hr) were performed to assess the sensitivity (effective concentration; ECx) of G. pectinatus to the target chemical compounds at the beginning and end of the exposure period. 8 Dissolved oxygen, salinity, and pH were measured with a multi-parameter (HQ40d, Hach®) before and after the replacement of the test solutions.…”
Section: Methodsmentioning
confidence: 99%